Molecular characterization of P80 gene of Indian Mycoplasma agalactiae isolates - Amin Kashoo, Zahid; Singh, Virendar Pal; Rana, Rajneesh; Sankar, Muthu; Gazalli, Humaira; Susan, SijSiju (The Indian Journal of Animal Sciences, 2011)
Serological tests are considered to be the most suitable for screening the goat pens for contagious agalactia, mainly caused by Mycoplasma agalactiae, but these have certain limitations due to the cross-reactive antigens among different mycoplasma species. The present study was undertaken to characterize the membrane protein p80 of M. agalactiae for specific diagnosis of disease as p80 protein is expressed in all field strains as well as throughout the course of infection. Five Indian isolates of M. agalactiae and one isolate of Mycoplasma bovis were used in the study after checking the purity by cultural examination, various biochemical tests and group specific and M. agalactiae specific PCR assays. Using group specific primers GPO-1 and MGSO, an amplified fragment ~715 bp was observed whereas, M. agalactiae specific PCR primers MboF2 and MboR2 produced an amplicon of size ~734 bp in all the 5 isolates. The cell lysates of all M. agalactiae isolates were subjected to SDS-PAGE western blot analysis, which resulted in a prominant band of ~80 kDa. The gene specific primers were designed and custom-synthesized for amplification of p80 which amplified the amplicon of 1014 bp from all strains. Our findings indicated that the membrane protein P80 is conserved antigen in the Indian isolates of M. agalactiae and can be used for specific diagnosis of contagious agalactia.